Ж.ГАНГААГИЙН ӨГҮҮЛЛИЙН ГАЙХАЛТАЙ ГАНЦ ДҮРСЛЭЛИЙН ТУХАЙ - Д. Батжаргал (Acta Mongolica, 2013)
Description is basic elements of article piece. In this article, the author urges the need for a dedicated study on the characteristics and skills of the writings by well-known Mongolian publicists and journalists, and promotes the author’s recognition for their publications.